The Habit of Midnight Prayer in Cultivating Spiritual Intelligence; Term of Surah Al-Isra: 79 - Anshori, Irfan; Wasehudin, Wasehudin (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
This research aims to measure the influence of students' understanding of Surah Al-Isra, verse 79, on the habituation of the Sunnah prayer of Tahajjud and its impact on spiritual intelligence. This research primarily focuses on examining the impact of students' understanding of the verse on their behavior, specifically in relation to their habit of performing the tahajud prayer and their spiritual intelligence. This is important because there are still students who, despite understanding the verse and practicing the tahajud prayer, continue to engage in negative behaviors. Teachers, students, and community leaders participate in interviews and questionnaires as part of the quantitative descriptive research method. Slovin's formula, with a margin of error of 10%, selected a research sample of 69 students from a population of 698 individuals. The results indicate that 76.4% of the students' understanding of Surah Al-Isra, verse 79, influences their spiritual intelligence. Additionally, the habit of performing Tahajjud prayers contributes 43.4% to the enhancement of students' spiritual intelligence. Overall, the relationship between the understanding of the verse, the habit of Tahajjud prayers, and spiritual intelligence mutually influences each other with a value of 76.9%. The implications of this study highlight the importance of improving students' understanding of Surah Al-Isra, verse 79, to encourage consistency in the practice of Tahajjud prayers, which can ultimately enhance spiritual intelligence. Teachers, educators, and policymakers in the pesantren environment can use this as a guide to design more effective educational programs that enhance spiritual intelligence through a religious approach. Penelitian ini bertujuan untuk mengukur pengaruh pemahaman santri terhadap surah al-Isra ayat 79 dalam membiasakan salat sunnah tahajud serta dampaknya terhadap kecerdasan spiritual. Fokus utama penelitian ini adalah meneliti bagaimana pemahaman terhadap ayat tersebut dapat memengaruhi perilaku santri, terutama terkait kebiasaan salat tahajud dan kecerdasan spiritual, mengingat masih adanya santri yang meskipun memahami ayat dan melaksanakan salat tahajud, namun tetap melakukan perilaku negatif. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan deskriptif, di mana data dikumpulkan melalui wawancara dan kuesioner yang melibatkan guru, siswa, dan tokoh masyarakat. Dari populasi sebesar 698 orang, sampel penelitian dipilih sebanyak 69 siswa menggunakan rumus Slovin dengan tingkat kesalahan 10%. Hasil penelitian menunjukkan bahwa 76,4% pemahaman santri terhadap surah al-Isra ayat 79 berpengaruh pada kecerdasan spiritual mereka. Selain itu, pembiasaan salat tahajud berkontribusi sebesar 43,4% terhadap peningkatan kecerdasan spiritual siswa. Secara keseluruhan, hubungan antara pemahaman ayat, kebiasaan salat tahajud, dan kecerdasan spiritual saling mempengaruhi dengan nilai sebesar 76,9%. Implikasi dari penelitian ini menunjukkan pentingnya meningkatkan pemahaman santri terhadap surah al-Isra ayat 79 untuk mendorong konsistensi dalam pelaksanaan salat tahajud, yang pada akhirnya dapat meningkatkan kecerdasan spiritual. Hal ini dapat menjadi panduan bagi guru, pendidik, dan pemangku kebijakan di lingkungan pesantren dalam merancang program pendidikan yang lebih efektif dalam meningkatkan kecerdasan spiritual melalui pendekatan keagamaan.